Temporal trends and factors associated with preterm birth in Chile, 1992-2018 - Carol Toro-Huerta; Carolina Vidal; Luis Araya-Castillo (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2023)
An analytical study based on Chilean birth records obtained from the Department of Statistics and Health Information (DEIS) was conducted. This study aimed to evaluate temporal trends in preterm births by maternal age in Chile from 1990 to 2018. Results show that the preterm birth rate in 1992 was 5.0% and increased to 7.2% in 2018. The average annual percent change (AAPC) was 1.44. Age groups at the extremes (19 and under and 35 and over) presented the highest rates of preterm birth, both at the beginning and at the end of the study period. The latter group showed a smaller decrease at the beginning (1992 to 1995), with an annual percentage change (APC) of -3.00. The probability of preterm birth in both groups was higher compared to the 20-34 year old group. Although Chile boasts some of the best maternal and child health indicators in the region, repercussions associated with the current postponement of maternity - including preterm birth - must be monitored.